My life as a Youtuber - Tashjian, Janet (Tashjian, Janet. My life series., 2020)
Derek Fallon and his friends take a class from a local comic with his own YouTube channel. The kids have the opportunity to create their own channels, but Derek learns that it's not that easy after suffering a series of humorous misfortunes and embarrassments.